Analysis of The Growth Rate, Effectiveness and Contribution of Regional Taxes to The Original Regional Revenue of Gorontalo Province for the Period 2020-2024 - Hapsa Yasin; Sahmin Noholo; Muliyani Mahmud (International journal of technology and education research, 2025)
This study aims to find out and analyze the growth rate, effectiveness, and amount of regional tax contribution to the original regional revenue of Gorontalo Province during the 2020-2024 period. The method used in this study is a descriptive method with a quantitative approach with the type of data used, namely secondary data. The analysis used is an analysis of growth rate, effectiveness and contribution. The results of this study show that the growth rate of regional taxes in Gorontalo Province during the 2020-2024 period shows unstable conditions and tends to fluctuate with an average of 5% included in the criteria of not succeeding. Meanwhile, the level of regional tax effectiveness in Gorontalo Province shows very good achievements with an average of 110%. Regional taxes make a huge contribution to the Regional Revenue of Gorontalo Province with an average of 84% which means that most of the original revenue of Gorontalo Province comes from regional taxes.